Welcome to Westonci.ca, where you can find answers to all your questions from a community of experienced professionals. Join our Q&A platform to connect with experts dedicated to providing precise answers to your questions in different areas. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
To convert the point-slope form of the line equation to the standard form, we need to follow a systematic sequence of algebraic steps. The given point-slope form of the equation is:
[tex]\[ y + 7 = -\frac{2}{5}(x - 10) \][/tex]
Let's break down the steps:
### Step-by-Step Solution
1. Initial form: The given point-slope form of the equation of the line is:
[tex]\[ y + 7 = -\frac{2}{5}(x - 10) \][/tex]
2. Clear the fraction by multiplying through by 5: This will help to eliminate the fraction and make the coefficients integers.
[tex]\[ 5(y + 7) = 5 \left( -\frac{2}{5} (x - 10) \right) \][/tex]
[tex]\[ 5(y + 7) = -2(x - 10) \][/tex]
3. Distribute and simplify:
[tex]\[ 5y + 35 = -2x + 20 \][/tex]
4. Rearrange terms to achieve the form [tex]\(ax + by = c\)[/tex]. We need to get all terms involving [tex]\(x\)[/tex] and [tex]\(y\)[/tex] on one side of the equation, and the constant on the other side.
[tex]\[ 2x + 5y = -15 \][/tex]
So, the standard form of the equation is:
[tex]\[ 2x + 5y = -15 \][/tex]
### Choosing the Correct Option
Among the provided choices:
- [tex]\( 2x - 5y = -15 \)[/tex]
- [tex]\( 2x - 5y = -17 \)[/tex]
- [tex]\( 2x + 5y = -15 \)[/tex]
- [tex]\( 2x + 5y = -17 \)[/tex]
The correct one is:
[tex]\[ 2x + 5y = -15 \][/tex]
Thus, the answer is:
[tex]\[ \boxed{2x + 5y = -15} \][/tex]
[tex]\[ y + 7 = -\frac{2}{5}(x - 10) \][/tex]
Let's break down the steps:
### Step-by-Step Solution
1. Initial form: The given point-slope form of the equation of the line is:
[tex]\[ y + 7 = -\frac{2}{5}(x - 10) \][/tex]
2. Clear the fraction by multiplying through by 5: This will help to eliminate the fraction and make the coefficients integers.
[tex]\[ 5(y + 7) = 5 \left( -\frac{2}{5} (x - 10) \right) \][/tex]
[tex]\[ 5(y + 7) = -2(x - 10) \][/tex]
3. Distribute and simplify:
[tex]\[ 5y + 35 = -2x + 20 \][/tex]
4. Rearrange terms to achieve the form [tex]\(ax + by = c\)[/tex]. We need to get all terms involving [tex]\(x\)[/tex] and [tex]\(y\)[/tex] on one side of the equation, and the constant on the other side.
[tex]\[ 2x + 5y = -15 \][/tex]
So, the standard form of the equation is:
[tex]\[ 2x + 5y = -15 \][/tex]
### Choosing the Correct Option
Among the provided choices:
- [tex]\( 2x - 5y = -15 \)[/tex]
- [tex]\( 2x - 5y = -17 \)[/tex]
- [tex]\( 2x + 5y = -15 \)[/tex]
- [tex]\( 2x + 5y = -17 \)[/tex]
The correct one is:
[tex]\[ 2x + 5y = -15 \][/tex]
Thus, the answer is:
[tex]\[ \boxed{2x + 5y = -15} \][/tex]
Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.